Alasan Penamatan Perjanjian di Bawah Akta Francais 1998 - Yaacob, Nurli (Kanun: Jurnal Undang-undang Malaysia, 2012)
This article aims to delve into the elements of "good cause" that can be used by franchisors to terminate franchise agreements as provided for by the Franchise Act 1998. The method used involved an interpretation of statutes and case studies based on cases decided by the court. The article purports to show that the grounds specified in the Franchise Act 1998 cater only for a franchisor to terminate a franchise agreement on the ground of "good cause." There is no provision for a franchisee to terminate the agreement based on "good cause." Therefore, it is proposed that both parties shall include additional grounds for termination of a franchise agreement before expiry of its duration in the franchise agreement signed by them. Keywords: grounds for termination; termination of contract; Franchise Act 1998; franchise agreement, good cause